On The Biological Phenomenon Of Nanoparticle-Cellular Protein Interactions - AFAF-EL-ANSARY,; ARJUMAND S.WARSY,; SOHAIR ALY HASSAN, (International Journal of Pharma and Bio Sciences, 2012)
It is now well accepted that material surfaces are modified by the adsorption of biomolecules such as proteins in a biological environment, and there is some consensus that cellular responses to materials in biological medium reflect the adsorbed biomolecule layer, rather than the material itself. However, the importance of the adsorbed protein layer mediating interactions with living systems has been slower to emerge in case of nanoparticle-protein "corona". This article represents a comprehensive review of previously published work related to this phenomenon in a trial to understand much of the bionanoscience world. Examples of nanoparticle- protein coronas will be reviewed. Understanding nanoparticle/protein interactions in an attempt to understand the distribution of the nanoparticles in the body, after absorption from different routes, and their interaction with different cell types and their accumulation or elimination, would represent a truly new aspect in the field of nanoscale studies, particularly the study of nanotoxicity, and in the design of nanocarriers for nanomedicine